1987
DOI: 10.1016/0014-2999(87)90299-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methadone on plasma arginine vasopressin level and urine production in conscious dogs

Abstract: The aim of this study was to examine the effect of i.v. methadone on the plasma arginine-vasopressin (AVP) levels and urine production in 9 conscious dogs. A highly significant increase from the baseline plasma AVP values of below 3 pg/ml occurred within 5 min following methadone administration. Maximum levels were reached within 30-50 min post-injection and varied from 18.5 to 100 pg/ml. A significant decrease in urine production was not seen under these experimental conditions. Mean arterial blood pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
1
9
1
2
Order By: Relevance
“…Infusion of hypertonic saline caused a similar, relative increase in plasma osmolality and plasma Na+ concentration (Table 1) (Szilagyi & Fer¬ rarlo 1986;Hellebrekers et al 1987), whereas at the high-dose level, naloxone was reported to in¬ crease the osmotic responsiveness of AVP (Wade 1985). Bromocriptine was administered at a dose, shown effectively to suppress pituitary interme¬ diate lobe secretion of prolactin (Janssens 1986).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Infusion of hypertonic saline caused a similar, relative increase in plasma osmolality and plasma Na+ concentration (Table 1) (Szilagyi & Fer¬ rarlo 1986;Hellebrekers et al 1987), whereas at the high-dose level, naloxone was reported to in¬ crease the osmotic responsiveness of AVP (Wade 1985). Bromocriptine was administered at a dose, shown effectively to suppress pituitary interme¬ diate lobe secretion of prolactin (Janssens 1986).…”
Section: Resultsmentioning
confidence: 96%
“…A VP extraction and radioimmunoassay Full details of the AVP extraction and radioimmuno¬ assay were described by us previously (Hellebrekers et al 1987). In short, plasma AVP was extracted using reversed-phase columns of octylsilane (C8) bonded silica gel (J. T. Baker Chemical Co, Phillipsburg, NJ).…”
Section: Experimentalprotocolmentioning
confidence: 99%
“…As a second mechanism of methadone induced bradycardia an increased baroreceptor activity secondary to increased vascular resistance mediated by elevation of arginine vasopressin plasma levels has been proposed (Hellebrekers et al. 1987, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…2007). In contrast, methadone has been shown to increase systemic vascular resistance and arterial blood pressure (Hellebrekers et al. 1987, 1989; Maiante et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation